Morphine and cocaine increase serum‐ and glucocorticoid‐inducible kinase 1 activity in the ventral tegmental area. (26th August 2014) - Heller, Elizabeth A.; Kaska, Sophia; Fallon, Barbara; Ferguson, Deveroux; Kennedy, Pamela J.; Neve, Rachael L.; Nestler, Eric J.; Mazei‐Robison, Michelle S.
Abstract Drugs of abuse modulate the function and activity of the mesolimbic dopamine circuit. To identify novel mediators of drug‐induced neuroadaptations in the ventral tegmental area (VTA), we performed RNA sequencing analysis on VTA samples from mice administered repeated saline, morphine, or cocaine injections. One gene that was similarly up‐regulated by both drugs was serum‐ and glucocorticoid‐inducible kinase 1 (SGK1). SGK1 activity, as measured by phosphorylation of its substrate N‐myc downstream regulated gene (NDRG), was also increased robustly by chronic drug treatment. Increased NDRG phosphorylation was evident 1 but not 24 h after the last drug injection. SGK1 phosphorylation itself was similarly modulated. To determine the role of increased SGK1 activity on drug‐related behaviors, we over‐expressed constitutively active (CA) SGK1 in the VTA. SGK1‐CA expression reduced locomotor sensitization elicited by repeated cocaine, but surprisingly had the opposite effect and promoted locomotor sensitization to morphine, without affecting the initial locomotor responses to either drug. SGK1‐CA expression did not significantly affect morphine or cocaine conditioned place preference, although there was a trend toward increased conditioned place preference with both drugs. Further characterizing the role of this kinase in drug‐induced changes in VTA may lead to improved understanding of neuroadaptations critical to drug dependence and addiction. <boxed-text content-type="graphic" id="jnc12925-blkfxd-0008" position="anchor" orientation="portrait"> </boxed-text> We find that repeated, but not acute, morphine or cocaine administration induces an increase in serum‐ and glucocorticoid‐inducible kinase (SGK1) gene expression and activity in the ventral tegmental area (VTA). This increase in SGK1 activity may play a role in drug‐dependent behaviors and suggests a novel signaling cascade for potential intervention in drug dependence and addiction.